2017
DOI: 10.19185/matters.201711000011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral responses to fishing line entanglement of a juvenile bottlenose dolphin in Shark Bay, Australia

Abstract: Entanglement in marine debris has become a serious matter for marine fauna, yet most data come from deceased animals. Here we studied a non-lethal entanglement event involving a female juvenile bottlenose dolphin (Tursiops aduncus), known as EDE, in Shark Bay, Western Australia who has been monitored and observed since birth as part of a long-term study. We compared her behavior before, during, and after entanglement. During entanglement, EDE markedly decreased time spent foraging, and increased time spent tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Dolphins are thus likely to remain in the system as long as adequate resources are available. However, abnormal dolphin mortality was not observed during the course of this study or by a contemporary study of mother–calf pairs (Miketa ), making it difficult to explain the declines observed here. While dolphins in Shark Bay forage on seagrass‐associated fishes, they are less dependent on seagrass for forage than cormorants or sea snakes (Heithaus and Dill , Heithaus , Sargeant et al.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Dolphins are thus likely to remain in the system as long as adequate resources are available. However, abnormal dolphin mortality was not observed during the course of this study or by a contemporary study of mother–calf pairs (Miketa ), making it difficult to explain the declines observed here. While dolphins in Shark Bay forage on seagrass‐associated fishes, they are less dependent on seagrass for forage than cormorants or sea snakes (Heithaus and Dill , Heithaus , Sargeant et al.…”
Section: Discussioncontrasting
confidence: 65%
“…, Miketa ). For example, a contemporary study in Shark Bay indicated that while seagrass associated dolphins used seagrass habitats more frequently after the heat wave, they reduced their foraging time in heavily damaged beds, instead foraging in relatively intact seagrass habitats (Miketa ). Similarly, cormorants in this system track prey densities even at fine, microhabitat scales (Heithaus ), and cormorants were more likely to use shallow habitats after the seagrass die‐off.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall, the SAOM framework enables to study how individuals change their relationships in response to the present network structure, i.e., group behavior ( 29 ). Despite its strong potential, SAOMs have been less explored in animal studies compared to social sciences studies [barbary macaques: ( 26 ); black-capped chickadees: ( 30 ); bottlenose dolphins: ( 31 ); crickets: ( 27 , 32 ); farmed salmons: ( 33 ); fruit flies: ( 34 ); rooks: ( 35 ); spiders: ( 36 ); spotted hyenas: ( 24 ); vervet monkeys: ( 37 )].…”
Section: Introductionmentioning
confidence: 99%
“…Observations of a bottlenose dolphin calf temporarily entangled in monofilament line showed immediate alterations in the behavior of the mother and calf, as well as conspecifics ( 71 ). A similar pattern of seemingly social avoidance by conspecifics following entanglement has occurred on a number of occasions [( 72 ) and references therein], where the costs of entanglement (e.g., infection, injury, energetic costs, inability to forage), are likely exacerbated. As well as causing distress to surviving family or social group members, the loss of key individuals may lead to the loss of important social knowledge ( 73 ).…”
Section: Welfare Impacts Associated With Bycatchmentioning
confidence: 77%